Analytical View on the Professional Characteristics and Qualities of the Modern Accountant - Atanasov, Atanas (Research Papers, 2023)
The article outlines and argues the public responsibility and importance of the accounting profession. Emphasis is placed on the range of professional competencies and moral and ethical qualities that are necessary for the full implementation of accounting activities and services. In conclusion, the study concludes that the outlined features predetermine the important and multifunctional role of the professional position of ”accountant”.
Keywords: Accounting profession; Accountant; Accounting work; Professional accountant; Accounting